2013
DOI: 10.1590/s1984-29612013000400010
|View full text |Cite
|
Sign up to set email alerts
|

New host records and a checklist of fishes infected with Austrodiplostomum compactum (Digenea: Diplostomidae) in Brazil

Abstract: This study reports the infection of fishes by Austrodiplostomum compactum metacercariae in the Chavantes reservoir, medium Paranapanema River, municipality of Ipaussu, São Paulo State, Brazil. Twenty-three fish species were analysed, and 13 were infected with A. compactum metacercariae (56.5%) in their eyes. The following six fish species are new hosts for this metacercaria: Crenicichla haroldoi (1/1), Eigenmannia trilineata (11/6), Hoplosternum littorale (11/1), Iheringichthys labrosus (17/2), Leporinus ambly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 34 publications
(28 reference statements)
0
21
0
Order By: Relevance
“…In the case of metacercariae of Austrodiplostomum sp., which were already recorded in several fish (a generalist species at that stage of development) in the São Francisco River and other basins (see RAMOS et al, 2013), they were able, as active cercariae, to infect fish (which acted as a second intermediate host) and achieved a good distribution among them across the aquatic environment. In this study, the fact that cercariae of the Austrodiplostomum sp.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In the case of metacercariae of Austrodiplostomum sp., which were already recorded in several fish (a generalist species at that stage of development) in the São Francisco River and other basins (see RAMOS et al, 2013), they were able, as active cercariae, to infect fish (which acted as a second intermediate host) and achieved a good distribution among them across the aquatic environment. In this study, the fact that cercariae of the Austrodiplostomum sp.…”
Section: Discussionmentioning
confidence: 67%
“…The parasites were processed and preserved according to Amato et al (1991) The prevalence (P) of Austrodiplostomum sp. varied among Siluriform fish (omnivorous adult representatives of Pimelodidae) from São Francisco River, and their rates were occasionally lower than that of adult digenean species in the parasite communities (P. maculatus: P=20.5%, lower than that of Plehniella coelomica Szidat, 1951(= Sanguinicola coelomica (Szidat, 1951 RAMOS et al, 2013). In some studies, those metacercariae showed a higher prevalence rate than the trahiras from the upper São Francisco River (P=60.7% in the Paraná River (SANTOS et al, 2012), and P=57.1% in the mid-Doce River, State of Minas Gerais (BELEI et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on parasitism in pimelodids have been also conducted in other localities of Brazil, such as some helminth parasites of species of Pimelodus Lacepède, 1803: P. blochii Valenciennes, 1840in Paraná River (KOHN et al, 1997; P. fur (Lütken, 1874) in Paraná River ; P. maculatus in Amazon Basin in Guaiba River (KOHN;FRÓES, 1986;FORTES et al, 1993;SARMENTO et al, 1995); in Guandu River (SANTOS et al, 2007;ALBUQUERQUE et al, 2008;AZEVEDO et al, 2010); in Itajaí-Açu River (BACHMANN et al, 2007); in Mogi Guaçu River (TRAVASSOS; KOHN, 1965;KOHN et al, 1985;FERNANDES, 1987;AGUIAR et al, 2011); in Paraiba do Sul River (VENANCIO et al, 2010); in Paraná River (TRAVASSOS; KOHN, 1965;MACHADO DOS SANTOS, 1992;MORAVEC et al, 1993MORAVEC et al, , 1997KOHN et al, 1997;PAVANELLI, 2004;KOHN, 2008;KOHN et al, 2011;LOPES et al, 2011); in Paranapanema River (RAMOS et al, 2013); Pimelodus microstoma Steindachner, 1877 in Mogi Guaçu River (AGUIAR et al, 2011) [note of the authors: this fish species was cited by the authors as P. heraldoi Azpelicueta, 2001, that is a junior synonym of P. microstoma Stein., sensu Ribeiro and Lucena (2010) KOHN, 2001;KOHN et al, 2011); Pimelodus sp. in Amazon Basin (VICENTE et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…These results corroborate the observations of Yamada et al (2008), who hypothesized that the larval stage of the parasite species has low specificity for the second intermediate host (fish). According to Ramos et al (2013), the majority of fish species infected with A. compactum metacercariae in Brazil belong to the orders Perciformes (12 species), Siluriformes (13 species) and Characiformes (nine species), and to the families Cichlidae (10 species) and Loricariidae (eight species). Moreover, with the record of the present study, the number of fish species infected with metacercariae of A. compactum in the order Characiformes has now increased to 10.…”
mentioning
confidence: 99%